Do Hospitals Affiliated With the Kurdistan University of Medical Sciences Perform Efficiently? Non-parametric Data Envelopment Analysis - Satar Rezaei; Nooredin Dopeykar; Mohsen Barouni; Mohammad Jafari; Fardin Gharibi (Baqiyatallah University of Medical Sciences, 2016)
Background: One way to improve the performance of hospitals, the largest resource-consuming units in the healthcare sector, is to continuously evaluate their performance. Objective: The current study assessed the performance of hospitals affiliated with the Kurdistan University of Medical Sciences using data envelopment analysis (DEA). Methods: This retrospective descriptive-analytic study used DEA to assess efficiency types (technical, managerial, and scale) in hospitals of the Kurdistan University of Medical Sciences (n = 12) in the years 2007 to 2011. The number of active beds, nurses, physicians (general and specialist), and other staff were inputs; inpatient admission and occupied bed days were outputs. Stata version 12 was used for data analysis. Results: The mean technical, scale, and managerial efficiency values were 0.85, 0.89, and 0.95, respectively. The highest and lowest slack inputs were nurses and active beds, respectively. Conclusion: The findings indicate that Kurdistan hospitals were less than appropriately efficient during the studied period. They also suggest that there is a capacity of about 15% for enhancing output in hospitals (compared with the most efficient studied hospitals) without increasing costs or inputs.